CD4+ T Lymphocytes with follicular helper phenotype (T FH) in patients with SH2D1A deficiency (XLP) - Coraglia, Ana Carina (2011)
Peripheral blood mononuclear cells with T FH phenotype from two asymptomatic XLP patients were studied. Normal/high numbers of CXCR5+, CD4+ T cells coexpressing PD-1 were demonstrated. Peripheral blood mononuclear cells (PBMC) from these patients responded to sub-optimal PHA/IL-2 stimulation upregulating ICOS and CD40L and increasing intracellular expression of IL-10, IL-21 and IL-4 by CD4+ T FH cells. However when compared to N, the time profile of activation and cytokine synthesis was different in XLP and N. While ICOS and CD40L expression in N decreased after 6-8days, it continued to increase or was maintained in XLP cultures. Intracellular IL-10, IL-21 and IL-4 reached higher values in XLP than N after 8days. Rather than the absence of T FH cells or their intrinsic inability to respond to stimuli, differences in the time profile of their response could contribute to impair their role as helpers of B lymphocytes. © 2011 Elsevier Inc.